MicroRNA-92a-3p enhances functional recovery and suppresses apoptosis after spinal cord injury via targeting phosphatase and tensin homolog. Issue 5 (4th May 2020) - He, Shaoxuan; Wang, Zhihua; Li, Yunxuan; Dong, Junjie; Xiang, Dong; Ren, Lirong; Guo, Limin; Shu, Jun
Abstract: Spinal cord injury (SCI) is a neurological disease commonly caused by traumatic events on spinal cords. MiRNA-92a-3p is reported to be down-regulated after SCI. Our study investigated the effects of up-regulated miR-92a-3p on SCI and the underlying mechanisms. SCI mice model was established to evaluate the functional recovery of hindlimbs of mice through open-field locomotion and scored by Basso, Beattie, and Bresnahan (BBB) locomotion scale. Apoptosis of spinal cord cells was determined by flow cytometry. The effects of miR-92a-3p on SCI were detected by intrathecally injecting miR-92a-3p agomiR (agomiR-92) into the mice prior to the establishment of SCI. Phosphatase and tensin homolog (PTEN) was predicted as a target of miR-29a-3p by TargetScan. We further assessed the effects of agomiR-92 or/and overexpressed PTEN on apoptosis rates and apoptotic protein expressions in SCI mice. Moreover, the activation of protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling was determined by Western blot. The results showed that compared with the sham-operated mice, SCI mice had much lower BBB scores, and theapoptosis rate of spinal cord cells was significantly increased. After SCI, the expression of miR-92a-3p was down-regulated, and increased expression of miR-92a-3p induced by agomiR-92 further significantly increased the BBB score and decreased apoptosis. PTEN was specifically targeted by miR-92a-3p. In addition, the phosphorylation levels of Akt and mTOR were up-regulated under the treatment of agomiR-92. Our data demonstrated that the neuroprotective effects of miR-92a-3p on spinal cord safter SCI were highly associated with the activation of the PTEN/AKT/mTOR pathway.